Relationship Between Motivational Orientations, Metacognitive Adaptations and Academic Successes of Doctorate Students - YEGEN, BERRAK; GÜLPINAR, MEHMET ALİ (DEOMED PUBL, ISTANBUL, 2018)
Motivational orientations and metacognitive adaptations displayed in difficult situations are the two major factors that affect the academic success of students. The aim of this study is to examine relationship between motivational orientations, metacognitive adaptations and academic successes of doctorate students attending to Health Sciences Institute. In this study conducted on 139 students The Modified Archer's Health Professions Motivation Survey, The Positive Metacognitions and Positive Meta-Emotions Questionnaire and performance evaluation forms were used. In the study where metacognitive adaptation levels of doctorate students were found high, their self-confidence levels in extinguishing perseverative thoughts and emotions were found to be significantly different in comparison to their levels of goal orientations towards performance, academic alienation and their use of superficial learning strategies. Their self-confidence levels in interpreting own emotions as cues, restraining from immediate reaction and mind setting for problem solving, establishing flexible and feasible hierarchy of goals were also found to be significantly different in comparison to their levels of academic alienation, use of metacognitive learning strategies, and internal control (p<0.05). It was also observed that academic success of the students at course and thesis stages were found to be significantly different as compared to their level of metacognitive learning strategies, self-confidence levels for setting flexible/feasible hierarchy of goals (p<0.05).
Keywords: Learner's characteristics; performance evaluation; postgraduate education; ACHIEVEMENT GOALS; MEDICAL-STUDENTS; PERFORMANCE; UNIVERSITY